Diastereoselective Pd-Catalyzed Decarboxylative Allylation To Construct Quaternary Stereocenters Using Sulfinimine as the Directing Group - Cao, Sheng; Li, Chen; Wang, Xuan; Huang, Yilei; Yang, Guang; Luo, Yunhao; Qin, Shuanglin (Synlett, 2021)
A robust Pd(0)-catalyzed decarboxylation alkylation has been developed to construct quaternary stereocenters through the use of chiral tert-butanesulfinamide as the directing group. This strategy provides a simple and efficient route to the construction of quaternary chiral centers at the α-position of chiral sulfinamides, with high diastereoselectivities and high yields.
Keywords: diastereoselective allylic alkylation; chiral quaternary stereocenters; chiral tert-butanesulfinamides; Pd(0)-catalyzed; β-sulfinimine esters